Tinjauan Tentang Tauhid - Madsuri (STIT Muslim Asia Afrika, 2019)
One of the fundamental religious guidelines is the necessity of respecting fellow human beings regardless of gender, race, ethnicity, and even religion, therefore every religion has two aspects of doctrine. That is the doctrine of the Deity and Humanity of Islam, for example has a teaching that emphasizes on two aspects at once. Vertical and horizontal aspects. The first contains a set of human obligations to God, while the latter contains a set of guidelines that govern the relationships between human beings and human relationships with the natural surroundings. Believing in Allah SWT, manifested in the first four faithful cases to the form of Allah SWT. Both believe in the Rubbubiyyah Allah SWT. All three believe in Uluhiyyah Allah SWT. The four believe in Substance, asthma nature and Af'al Allah SWT. Thus, it appears that monotheism is not merely a static religious doctrine. It is an active energy that enables humans to place God as God and humanity as human beings. The inspiration of the meaning of tawhid not only brings the benefit and salvation of the individual, but also gives birth to a moral, polite, humane, free and discriminating society, injustice, injustice, fear, stronger individual or group oppression, Tawheed as a center and the basis of belief in Islam is the source of the totality of people's attitudes and worldviews in the whole dimension of life. That is what has been done by the Prophet Muhammad SAW.